Pelatihan Pembuatan Media Pembelajaran Berbasis Articulate Storyline 3 di Sekolah Dasar - Salsabillah; MZ, A.F. Suryaning Ati; Mudayan , Arfian; Widiyanti, Wiwid (Universitas Mataram, 2024)
The implementation of this training activity aims to improve the abilities and skills of teachers at SD Muhammadiyah 1 Taman Sidoarjo in creating articulate storyline 3-based learning media. Through the training and mentoring carried out, the training participants can master the creation and use of the articulate storyline 3 application and successfully create learning media based on articulate storyline 3. This is a solution to various kinds of learning problems. The training targets who will be involved in this activity are all teachers at SD Muhammadiyah 1 Taman Sidoarjo. The method that will be carried out is the training planning stage for teachers using the articulate storyline 3 application, preparing materials for making learning media using the articulate storyline 3 application, preparing activity proposals, coordinating with partners, and providing tools and materials that will be used in training activities. The second stage is the implementation of training in creating learning media based on Articulate Storyline 3. In the evaluation stage, there are several activities, including checking the completeness of assignments in the form of digital learning media created using the Articulate Storyline 3 application by training participants, as well as giving posttests to participants. The evaluation results show that the assessment for creating articulate storyline 3 based learning media obtained a result of 89.08 with very good criteria. Meanwhile, the posttest results of the training participants obtained a result of 93.5 in the very good category. The evaluation results also show that the majority of training participants do not have experience, so this training material provides useful new knowledge. Increased teacher competency, and all participants are willing to apply training materials in creating learning materials. By improving skills in creating digital-based learning media, teachers can optimize the learning process. The results of community service that have been carried out, namely the success of implementing community service activities, apart from being measured from the components above, can also be seen from participant satisfaction after participating in training activities. Conclusion: The implementation of community service activities has been carried out well and the teacher is able to create articulate storyline-based learning media 3.